(untitled) (Revista de Biología Marina y Oceanografía, 2019)
The spiny lobster Panulirus pascuensis stands out among the endemic species of Easter Island, due to its cultural and economic importance. A total of 16 microsatellite loci were characterized in 18 individuals, 9 of which were polymorphic. The mean number of alleles per locus was 3.44 (2-6) and the observed heterozygosity ranged from 0.11 to 0.93. None of the loci exhibited significant linkage disequilibrium or departures from HWE. These new microsatellites will be used to obtain information about migration, population structure and genetic diversity of P. pascuensis in order to improve the future sustainable management and conservation plans.